2013
DOI: 10.1111/apha.12197
|View full text |Cite
|
Sign up to set email alerts
|

Maternal western diet primes non‐alcoholic fatty liver disease in adult mouse offspring

Abstract: Maternal dietary fat intake during early development programmes susceptibility to liver disease in male offspring, mediated by disturbances in lipid metabolism and inflammatory response. Long-lasting epigenetic changes may underlie this dysregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
66
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 49 publications
(77 reference statements)
2
66
0
Order By: Relevance
“…Evidence was found of early steatohepatitis similar to type II NASH, which is the most usual in paediatric NAFLD (Schwimmer et al 2005). Occurrence of NAFLD after prenatal programming has been previously found in male mice and not in female mice, but in the first generation and during adulthood (Pruis et al 2014), which supports the susceptibility of the Iberian pigs to changes in nutritional and metabolic status.…”
Section: Discussionmentioning
confidence: 53%
“…Evidence was found of early steatohepatitis similar to type II NASH, which is the most usual in paediatric NAFLD (Schwimmer et al 2005). Occurrence of NAFLD after prenatal programming has been previously found in male mice and not in female mice, but in the first generation and during adulthood (Pruis et al 2014), which supports the susceptibility of the Iberian pigs to changes in nutritional and metabolic status.…”
Section: Discussionmentioning
confidence: 53%
“…However, this effect is markedly exaggerated when the dams and offspring (CAF-CAF F1 ) have been exposed to CAF diet throughout life. As previously demonstrated by Bruce et al (2009) and Pruis et al (2014), the higher hepatic lipid accumulation in offspring could be attributed to up-regulation of de novo fatty acid synthesis, failure to up-regulate mitochondrial beta oxidation and fatty acid export. Animal models indicate that programmed effects, in particular hepatic steatosis, are highly irreversible after weaning.…”
Section: Maternal Diet Leads To Morphological Changes In Offspring 2895supporting
confidence: 52%
“…In contrast, Bringhenti et al (2011) reported that introducing fish oil to a post weaning diet can reverse maternal low protein diet induced hepatic steatosis in offspring. It probable that epigenetic events induced by maternal overnutrition leads to altered DNA methylation pattern of the offspring during their development and influencing their later health (Pruis et al 2014).…”
Section: Maternal Diet Leads To Morphological Changes In Offspring 2895mentioning
confidence: 99%
“…As an editor, you actually have a chance to get to the bottom of this question by taking a measure for quality (downloads or citations) and correlating that with the referees' scoring. The results are indeed surprising, as demonstrated by our five most cited original articles in 2014 (Boushel et al 2014, Pruis et al 2014, Yu et al 2014(Chen et al 2015, Dahl et al 2015, Heimlich et al 2015, Tam et al 2015, Uchida et al 2015.…”
mentioning
confidence: 84%